It's not about the burqa: Muslim women on faith,feminism, sexuality and race - Khan, Mariam (London: Picador, 2019)
In 2016, Mariam Khan read that David Cameron had linked the radicalization of Muslim men to the'traditional submissiveness' of Muslim women. Mariam felt pretty sure she didn't know a single Muslim woman who would describe herself that way. Why was she hearing about Muslim women from people who were neither Muslim, nor female? Years later the state of the national discourse has deteriorated even further, and Muslim women's voices are still pushed to the fringes - the figures leading the discussion are white and male. Taking one of the most politicized and misused words associated with Muslim women and Islamophobia, It's Not About the Burqa is poised to change all that. Here are voices you won't see represented in the national news headlines: seventeen Muslim women speaking frankly about the hijab and wavering faith, about love and divorce, about feminism, queer identity, sex, and the twin threats of a disapproving community and a racist country. With a mix of British and international women writers, from activist Mona Eltahawy's definition of a revolution to journalist and broadcaster Saima Mir telling the story of her experience of arranged marriage, from author Sufiya Ahmed on her Islamic feminist icon to playwright Afshan D'souza-Lodhi's moving piece about her relationship with her hijab, these essays are funny, warm, sometimes sad, and often angry, and each of them is a passionate declaration calling time on the oppression, the lazy stereotyping, the misogyny and the Islamophobia. What does it mean, exactly, to be a Muslim woman in the West today? According to the media, it's all about the burqa. Here's what it's really about.
Introduction / Mariam Khan --Chapter1:'Too Loud, Swears Too Much and Goes Too Far' / Mona Eltahawy -- Chapter 2:'Immodesty is the Best Policy' / Coco Khan -- Chapter 3:'The First Feminist' / Sufiya Ahmed --Chapter4:'On the Representation of Muslims: Terms and Conditions Apply' / Nafisa Bakkar -- Chapter 5:'The Clothes of My Faith' by Afia Ahmed -- Chapter 6:'Life was Easier Before I was Woke' Yassmin Midhat Abdel-Magied -- Chapter 7:'There's No Such Thing as a Depressed Muslim' by Jamilla Hekmoun -- Chapter 8:'Feminism Needs to Die' / Mariam Khan --Chapter 9:'Hijabi (R)evolution' / Afshan D'souza-Lodhi -- Chapter10:'Eight Notifications' / Salma Haidrani -- Chapter11:'Shame, Shame, It Knows Your Name' / Amna Saleem -- Chapter 12:'A Woman of Substance' / Saima Mir -- Chapter 13:'A Gender Denied: Islam, Sex and the Struggle to Get Some' / Salma El-Wardany -- Chapter 14:'How Not to Get Married (or why an unregistered nikah is no protection for a woman)' / Aina Khan OBE -- Chapter 15:'Not Just a Black Muslim Woman' by Raifa Rafiq -- Chapter16:'Between Submission and Threat - the British State's Contradictory Relationship with Muslim Women' / Malia Bouattia -- Chapter17:'Daughter of Stories' / Nadine Aisha Jassat
Keywords: Muslim women -- Social conditions; Muslim women -- Western countries -- Social conditions